Cytotoxicity of Donor Natural Killer Cells to Allo-Reactive T Cells Are Related With Acute Graft-vs.-Host-Disease Following Allogeneic Stem Cell Transplantation - Sheng, Lixia; Mu, Qitian; Wu, Xiaoqing; Yang, Shujun; Zhu, Huiling; Wang, Jiaping; Lai, Yanli; Wu, Hao; Sun, Ye; Hu, Yongxian; Fu, Huarui; Wang, Yi; et al. (Frontiers in immunology, 2020)
The mechanism and immunoregulatory role of human natural killer (NK) cells in acute graft-vs.-host-disease (aGVHD) remains unclear. This study quantitatively analyzed the cytotoxicity of donor NK cells toward allo-reactive T cells, and investigated their relationship with acute GVHD (aGVHD). We evaluated NK dose, subgroup, and receptor expression in allografts from 98 patients who underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT). A CD107a degranulating assay was used as a quantitative detection method for the cytotoxic function of donor NK cells to allo-reactive T cells. In antibody-blocking assay, NK cells were pre-treated with anti-DNAM-1(CD226), anti-NKG2D, anti-NKP46, or anti-NKG-2A monoclonal antibodies (mAbs) before the degranulating assay. NK cells in allografts effectively inhibited auto-T cell proliferation following alloantigen stimulation, selectively killing alloantigen activated T cells. NKG2A NK cell subgroups showed higher levels of CD107a degranulation toward activated T cells, when compared with NKG2A subgroups. Blocking NKG2D or CD226 (DNAM-1) led to significant reductions in degranulation, whereas NKG2A block resulted in increased NK degranulation. Donor NK cells in the aGVHD group expressed lower levels of NKG2D and CD226, higher levels of NKG2A, and showed higher CD107a degranulation levels when compared with NK cells in the non-aGVHD group. Using univariate analysis, higher NK degranulation activities in allografts (CD107a ) were correlated with a decreased risk in grade I-IV aGVHD (hazard risk [HR] = 0.294; < 0.0001), grade III-IV aGVHD (HR = 0.102; < 0.0001), and relapse (HR = 0.157; = 0.015), and improved overall survival (HR = 0.355; = 0.028) after allo-HSCT. Multivariate analyses showed that higher NK degranulation activities (CD107a ) in allografts were independent risk factors for grades, I-IV aGVHD (HR = 0.357; = 0.002), and grades III-IV aGVHD (HR = 0.13; = 0.009). These findings reveal that the degranulation activity of NK in allografts toward allo-activated T cells was associated with the occurrence and the severity of aGVHD, after allogeneic stem cell transplantation. This suggested that cytotoxicity of donor NK cells to allo-reactive T cells have important roles in aGVHD regulation.